Generation of graphene oxide and nano-bioglass based scaffold for bone tissue regeneration. (1st November 2022) - Kumari, Shikha; Singh, Divakar; Srivastava, Pradeep; Singh, Bhisham Narayan; Mishra, Abha
Abstract: Graphene oxide (GO) offers a distinct opportunity in the field of biomedical engineering owing to its exceptionally high mechanical strength, excellent electrical conductivity, high optical transparency, and favorable biocompatibility. In this article, nanocomposite biocompatible GO-based scaffolds (chitosan/gelatin/nanobioglass/GO) Ch-G-NBG-GO were successfully fabricated through freeze drying technique (−40 °C) and evaluated for various physico-chemical and biological properties. The prepared Ch-G-NBG-GO composites have been investigated for their structural, physiochemical, and surface morphology via x-ray diffraction (XRD), high resolution scanning electron microscope, Fourier transform infrared spectroscopy, thermogravimetric analysis (TGA), energy-dispersive x-ray Spectroscopy and, differential scanning colorimetry (DSC) respectively. The morphological analysis showed the porous interconnected network of scaffold formed. Average pore size for the Ch-G-NBG-GO scaffolds were in between 90 and 120 μm, which was very close to the control scaffolds. XRD data revealed the successful incorporation of NBG and GO and distribution across the scaffolds. Porosity of the fabricated scaffolds were in the range between 75.3% and 77.3% which was very close to the control scaffold with 79% porosity. The studies also reveal that after GO incorporation, the weight loss reduced (0.11 ± 0.02–0.095 ± 0.03), scaffolds were firmly stable at room temperature even after a long duration of 28 d. The crystallinity added to the scaffolds due to addition of GO nanoparticles improved the mechanical strength of these scaffolds. The compressive modulus changed from (5.7 to 8.51) MPa after GO addition. Swelling ratio changed drastically especially in case of Ch-NBG-90%GO (4.9 ± 0.04–4 ± 0.01). DSC and TGA data revealed the thermal stability of GO incorporated scaffolds due to the proper interaction between GO/NBG with chitosan-gelatin blend. The scaffold's potential for bone tissue engineering was evaluated by testing its cytocompatibility for MG-63 cell line. It revealed suitable cell attachment and proliferation of cells compared to the Ch-G-NBG scaffold. MTT assay showed that Ch-G-NBG-GO scaffold below 90% GO concentration possess best biocompatibility. But in case of Ch-G-NBG-90%GO scaffold, the cell proliferation was reduced when compared to control scaffolds. Alkaline phosphatase activity suggested improved osteogenic differentiation of MG-63 cells over GO based scaffolds and this was due to the osteogenic potential of NBG and GO present in the scaffolds. Based on these results, the nano-biocomposite scaffold appears to have the potential for utilization in bone tissue restoration, replacement and regeneration.